Compilation of the Public Acts of the Legislative Council of the Territory of Florida, Passed Prior to 1840 423 (1839), ch. 860 - (:unkn) unknown (General Publisher, 1835)
Prohibited the concealed carry of arms of any kind whatsoever. Also prohibited the carry of any dirk, pistol, or other arm, or weapon.
--
Keywords: CARRY - CONCEALED